Fitrah and Fitrah-Based Children's Education Concept in the Digital Era: The Perspective from Al-Qur'an and Hadith - Rezki Sulfitri Amir Fitri; Didin Hafidhuddin; Hasbi Indra; Adian Husaini (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Deviations from human nature cause moral crises, natural crises and life crises. One of the causes is neglect of children's potential and not paying attention to their development by providing good education. One solution is to restore the education system in accordance with the guidance of the Prophet, namely education based on nature, educating faith from an early age so that it develops in the direction it should and produces noble morals and gives birth to piety. This research is qualitative research with literature study. The data collection technique emphasizes aspects of text analysis and study. The method used is the tafsir maudhu'i and tafsir tahlili methods by collecting all the verses related to fitrah, then analyzing and explaining the meanings contained in these verses. Then analyze the implications of nature in children's education. Research shows that the foundation of fitrah-based education is the Koran, hadith, ijma' and qiyas. The aim is to strengthen the foundation of faith in children, give birth to people with noble character, give birth to people who always preserve nature and give birth to people whose obsession is the afterlife and whose goal is the approval of Allah. The educational materials are: faith education, moral education, intellectual education, soul education. Some of the challenges from the side of educators and students are lack of attention and awareness about the importance of education, disharmonious relationships between educators and students, lack of understanding and competence, material that accumulates and does not pay attention to the abilities and potential of each child, material that prioritizes the worldly rather than the ukhrawi aspect, lack of digital access and content that is not educational.